HUBUNGAN PERILAKU PEMELIHARAAN DENGAN KONDISI GIGI TIRUAN LEPASAN PADA MASYARAKAT DI WILAYAH KERJA PUSKESMAS BANDARHARJO KOTA SEMARANG - Vrishelli Setiadi Putri; Henry Setyawan Susanto; Retno Hestiningsih; Ari Udijono (Jurnal Kesehatan Masyarakat (Undip), 2017)
Denture are tools made to replace missing teeth and soft tissues around them.  Removable denture is divided into complete denture and partial denture. Denture can cause the mucosa under the denture to be closed for long periods of time, than blocking the cleaning of mucosal surfaces and denture by tongue and saliva.The aim of this sudyisto analyze the condition of removable denture to the community in the work area of Bandarharjo Puskesmas Semarang. This type of research is an observational analytic with cross sectional design. The technique sampling is total sampling.The variable analyzed by using phi Correlation test.The result showed that there were correlation of behavior (x2 = 0,023) with removable denture condition.  Respondents are suggested to brushing their teeth correctly, removed the denturebefore sleep and soak the denture.